Perspectives on presidential leadership (New York)
1 online resource (256 pages)
Keywords: In 2011 Barack Obama invited ten distinguished biographers to the White House to ask them one question: which past American president should I emulate? This was not the first time Obama asked scholars this, but the answer he received would differ as presidential legacies waxed and waned. In 2008 Obama chose Lincoln; in 2009, Reagan; and in 2010, Theodore Roosevelt. Perspectives on Presidential Leadership is an examination of presidential legacy, and in particular an analysis of the first ever UK ranking of American presidents which took place in 2011. In thirteen chapters, thi.